Baker Exegetical Commentary on the New Testament: Revelation - Osborne, Grant R. (Grand Rapids, Mich. : Baker Academic, 2002)
"The Book of Revelation contains some of the most difficult passages in Scripture. Grant Osborne's commentary on Revelation aims to interpret the text while also introducing readers to the perspectives of contemporary scholarship in a clear and accessible manner.Osborne begins with a thorough introduction to Revelation and the many difficulties involved in its interpretation. He discusses authorship, date of writing, and the social and cultural setting of the work. He also examines elements that complicate the interpretation of apocalyptic literature, including the use of symbols and figures of speech, Old Testament allusions, and the role of prophetic prediction. Osborne surveys various approaches commentators have taken on whether Revelation refers primarily to the past or to events that are yet future.Osborne avoids an overly technical interpretative approach. Rather than exegeting the text narrowly in a verse-by-verse manner, he examines larger sections in order to locate and emphasize the writer's central message and the theology found therein. Throughout, he interacts with the best recent scholarship and presents his conclusions in an accessible manner. When dealing with particularly problematic sections, he considers the full range of suggested interpretations and introduces the reader to a broad spectrum of commentators. As with all volumes published in the Baker Exegetical Commentary on the New Testament, Revelation seeks to reach a broad audience with scholarly research from a decidedly evangelical perspective. Each volume in the BECNT series interacts with the best contemporary scholarship, offering up-to-date, accurate, and authoritative analysis of the Greek text through rigorous exegesis and exposition. Central themes are developed throughout, and each exegetical unit is related to the overall message of the biblical book. Pastors and seminarians especially appreciate the combination of broad overview and in-depth analysis found in BECNT volumes, but the series is also popular with scholars and thoughtful lay readers" -- Publisher description.
Prologue (1:1-8) -- Churches addressed (1:9-3:22). Inaugural vision (1:9-20) ; Letters to the seven churches (2:1-3:22) -- God in majesty and judgment (4:1-16:21). God's sovereignty in judgment (4:1-11:19) ; Great conflict between God and the forces of evil (12:1-16:21) -- Final judgment at the arrival of the Eschaton (17:1-20:15). Destruction of Babylon the Great (17:1-19:5) ; Final victory : the end of the evil empire at the Parousia (19:6-21) ; The thousand-year reign of Christ and final destruction of Satan (20:1-10) ; Great white throne judgement (20:11-15) -- New heaven and new earth (21:1-22:5). Coming of new heaven and new earth (21:1-8) ; New Jerusalem as the Holy of Holies (21:9-27) ; New Jerusalem as the final Eden (22:1-5) -- Epilogue (22:6-21).
Includes bibliographical references (p. 801-824) and indexes.
Keywords: Bible. -- Commentaries